Anaesthetic management in COVID-19 parturients scheduled for caesarean delivery - a comparison with non-COVID-19 parturients - Singh, Ranju; Singh, Pooja; Neelakandan, Eashwar; Pandey, Maitree; Puri, Manju; Nangia, Sushma (International Journal of Research in Medical Sciences, 2021)
Background: Data regarding outcomes after anaesthesia in COVID-19 parturients is scanty. There is hardly any information about the length of hospital stay in COVID-19 parturients who undergo caesarean delivery (CD) as compared to non-COVID-19 parturients. Methods: An observational study of COVID-19 parturients undergoing CD was conducted. Age and CD indication matched non COVID-19 parturients were taken as controls. The length of hospital stay along with maternal and neonatal outcomes were studied. Results: A total of 45 COVID-19 parturients and an equal number of non-COVID-19 parturients were studied. The length of hospital stay was significantly longer in COVID-19 parturients as compared to non-COVID-19 parturients (4.3±1.6 days versus 3.3±0.6 days, p=0.02). One COVID-19 parturient developed severe disease and expired. Apart from this case, the maternal and neonatal outcomes were comparable between the two groups. Mild thrombocytopenia was seen in COVID-19 parturients. One neonate had a positive reverse transcriptase polymerase chain reaction (RT-PCR) for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) on first day of life. Conclusions: COVID-19 parturients who undergo CD have a longer length of hospital stay than non-COVID-19 parturients. Severe disease is likely to be associated with longer length of hospital stay. Intraoperative hypotension, maternal and neonatal outcome is not significantly different between COVID-19 and non COVID-19 although mild thrombocytopenia is seen in COVID-19 parturients. While vertical transmission of SARS-CoV-2 may be possible, more data is needed regarding vertical transmission is needed.